2021
DOI: 10.5664/jcsm.8798
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a patient decision aid for improving person-centered decision-making by older adults with obstructive sleep apnea

Abstract: In order to provide subscribers with access to new scientific developments as early as possible, accepted papers are posted prior to their final publication in an issue. These papers are posted as received-without copyediting or formatting by the publisher. In some instances, substantial changes are made during the copyediting and formatting processes; therefore, the final version of the paper may differ significantly from this version.Unless indicated otherwise, all papers are copyright of the American Academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…18,19 A randomized controlled trial of adults over 60 years-old showed that a decision aid program to engage patients in OSA therapy increased knowledge about treatment options, lowered DC, and allowed for greater preparedness for decision-making. 20 Our study demonstrates the need for interventions that can reduce decisional conflict and promote equitable knowledge about OSA treatment efficacy, risks, and benefits. Prior work on decision aids for adults with sleep apnea has largely been centered on patients with newly diagnosed OSA, and there remains a need for similar tools for patients considering alternative treatments.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…18,19 A randomized controlled trial of adults over 60 years-old showed that a decision aid program to engage patients in OSA therapy increased knowledge about treatment options, lowered DC, and allowed for greater preparedness for decision-making. 20 Our study demonstrates the need for interventions that can reduce decisional conflict and promote equitable knowledge about OSA treatment efficacy, risks, and benefits. Prior work on decision aids for adults with sleep apnea has largely been centered on patients with newly diagnosed OSA, and there remains a need for similar tools for patients considering alternative treatments.…”
Section: Discussionmentioning
confidence: 79%
“…Specifically with regards to OSA, randomized controlled trials of parents of children with OSA have demonstrated that use of decision aids lowers DC and increases adherence to CPAP treatment 18,19 . A randomized controlled trial of adults over 60 years‐old showed that a decision aid program to engage patients in OSA therapy increased knowledge about treatment options, lowered DC, and allowed for greater preparedness for decision‐making 20 …”
Section: Discussionmentioning
confidence: 99%
“…47 The PDA can also significantly improve patients’ ability to analyze the advantages and disadvantages of nutritional interventions, reduce their blindness and uncertainty, increase their participation in the decision-making process, and help them prepare for decision-making. 48 The decision conflict was significantly reduced because the patients felt informed about the pros and cons of nutrition modification, felt uncertain about the options, felt supported in making decisions, and had clear values of their own. However, we did not find any difference in anxiety after the use of the PDA in our study, which is consistent with the finding of Cox.…”
Section: Discussionmentioning
confidence: 99%
“…Person-centered care requires a collaborative approach to align individual values with attainable outcomes that often require an understanding of a patient's decisional conflict, health literacy, and preparedness for decision-making. 34 Patient and physician priorities require time and expertise to align in older adults with complex co-morbidities, yet investigators often neglect these factors in reporting the application of an intervention and implementation strategy in research. 35 Memory and communication impairments associated with Alzheimer's dementia and related disorders also create obstacles to both research consent and patientreported outcomes, so implementation researchers need to accommodate those challenges.…”
Section: Stari Outcomesmentioning
confidence: 99%